The characteristics of carbonaceous aerosol in Beijing during a season of transition. (December 2018) - Liu, Jiu-meng; Du, Zhen-yu; Gordon, Mark; Liang, Lin-lin; Ma, Yong-liang; Zheng, Mei; Cheng, Yuan; He, Ke-bin
Abstract: Carbonaceous aerosol was measured during fall of 2010 in Beijing. Daily variation of organic carbon (OC) was found to coincide with that of relative humidity (RH), and the OC to elemental carbon (EC) ratios were more than doubled during the more humid periods (RH above 0.75) compared to other conditions. This large increase in OC/EC could not be explained by the variations of primary biomass burning emissions but was accompanied by a five-fold increase in the sulfate to EC ratio. It was then inferred that secondary organic aerosol (SOA) formation was enhanced under the more humid conditions, presumably through aqueous-phase processes. This enhanced SOA formation might be partially associated with particles externally mixed with black carbon, as indicated by the RH-dependent relationships between aerosol optical attenuation and EC loading. In addition, organic aerosols exhibited different properties between the more humid and the other periods, such that they were less volatile and charred more significantly during thermal-optical analysis in the former case. These differences coincided with the evidence of enhanced SOA formation under the more humid conditions. This study highlights the necessity of incorporating aqueous-phase chemistry into air quality models for SOA. Highlights: OC/EC were more than doubled during the more humid periods than the other conditions. The large increase in OC/EC could not be explained by biomass burning emissions. The large increase in OC/EC was accompanied by a five-fold increase in sulfate/EC. OA were less volatile and charred more significantly during the more humid periods.